The role of phonological awareness in promoting Teaching Arabic reading and writing strategies according to the syllabic method: Moroccan and Qatari schools as a model. [In Arabic] - Mostafa Bouanani; Alaa Youssef Alkahlout (آموزش زبان، ادبیات و زبانشناسی, 2020)
Reading and writing are important in the process of learning and developing a child's knowledge in all fields of learning, which are the two basic skills on which the act of possessing and enriching knowledge is based on the long evolutionary path of learning of the child as long as all the details of knowledge are addressed to him through language. While taking that into consideration, modern global educational approaches and strategies, and educational curricula adopted in private and public educational institutions, tend to exploit the wealth of intellectual and scientific production accumulated by research and studies in all areas of cognitive science. One aspect of the cognitive learning breakthrough achieved by the accumulation of this cognitive research: linguistic, psychological, neurological is the profound change that has reached the essence of teaching trends in many countries. It became clear that the development of our perceptions of understanding the components of the brain, its functions and methods of functioning, and its treatment of linguistic information, was an important reason for the trend towards new paths in the development of programs and approaches related to literacy and teaching. On the basis of two field studies conducted in Morocco and Qatar on 120 learners from the first and second years of the primary corps our research paper will attempt to ascertain the impact of phonological awareness on literacy pathways by answering three central questions: Can the supposed correlation between phonological awareness and Arabic literacy be established in different Arabic language learning contexts? Are there any specificities that characterize this relationship in relation to variables related to educational institutions and the educational approaches adopted in them? Do the results of these studies confirm that the evolutionary path of learning is subject to the manifestations of the synergy of the phonology and spelling through the years of learning in order to possess the constants of Arabic reading and writing?